Strategic management as a catalyst for competitiveness in the logistics SMEs of the Atlántico department - Colombia (2019)
The research is aimed at determining the correlation of strategic management as a catalyst for competitiveness in SMEs in the logistics sector in the department of Atlántico - Colombia. The theme was developed from a quantitative and descriptive approach, for which the variables strategic management and competitiveness were operationalized, forming six (6) dimensions. The results reveal that there is a direct and positive correlation between the variables analyzed in the companies under study. For this reason, an instrument with 28 items was designed, whose reliability was validated by the Cronbach's Alpha, obtaining a value of ,957 considered excellent.